A Concise Review of Synthetic Strategy, Mechanism of Action, and SAR Studies of Phthalazine Derivatives as Anticancer Agent - Arya, Girish Chandra; Sharma, Rajiv; Mehla, Shefali (Letters in Drug Design & Discovery, 2024)
Background Colorectal cancer is the third foremost cause of death in women and men. Globally, about 1.94 million colon cancer cases were diagnosed and around 0.93 million patients died in the previous year. Introduction Several drugs have been permitted by the Food And Drug Administration (FDA) for the treatment of colorectal cancer. The main difficulties of current drugs are the expansion of resistance issues, target selectivity issues and toxicity issues. The existing therapies, such as surgery and hormonal therapy, are in use but exhibit numerous adverse effects, such as pharmacokinetic issues and pharmacodynamic issues. Hence, hereby is a crucial requirement of novel moieties that are peaceable and efficient in the handling of colorectal cancer. Methods Phthalazine derivatives have expanded admiration over a few years due to their efficient anticancer significance. These Phthalazine derivatives exhibit anticancer activity by targeting various mechanisms such as apoptosis induction, tubulin polymerization inhibition, EGFR inhibition, and aurora kinase inhibition. Results In this study, we have focused on the Structural Activity relationship, numerous synthetic strategies and mechanism of action of phthalazine derivatives for potential treatment of cancer. Conclusion Among some of phthalazine derivative compounds not only induced antiproliferative activity even also improve bioavailability and reduce side effects, like 4-(phthalazine-1-yl) aniline with (IC50 = 0.22 ± 0.11 μM), and 4-phthalazin-1-yl-amino) benzonitrile (IC50 = 1.20 μM), 4-((5-methyl-pyrazole-3-yl) amino)-2-phenylphthalazin-1-one (IC50 = 0.031 μM) and 4-((5-methyl-pyrazole-3-yl) amino)-2-(p-tolyl)phthalazin-1-one (IC50 = 0.065 μM). Therefore, this study would be the inspiration for the betterment of human health.
Keywords: synthetic strategies